IMPACT OF HEAVY METAL TO FISH AQUACULTURE IN FLOATING NET CAGE IN CIRATA RESERVOIR, INDONESIA - Tri Heru Prihadi; Murniyati Murniyati; Idil Ardi (Indonesian Aquaculture Journal, 2008)
Utilization of Cirata Reservoir for fisheries aquaculture with floating net cage system has been increasing rapidly. Industrial waste existed along watershed brings significant heavy metal pollutant that flows and difficult to control. Consequences of such activities were reflected in the degradation of reservoir environment indicated by sedimentation, water quality degradation and fish mass mortality because of up welling. The objectives of this research were: 1) to obtain data and information on heavy metal content in Cirata Reservoir waters, and 2) to observe and understand the effect of heavy metal to the fish cultured in floating net cage to support aquaculture in floating net cage system. Water quality and fish histology analyses were the methodologies used in this research. Descriptive and laboratory analysis were carry out to analysis the data. Based on observation and descriptive analyses, the content of heavy metal in Cirata Reservoir was classified as worse. Concentration of Pb, Cr, Hg, and Cd in the sample of water and tilapia digestive organ becomes fragile. Infiltration of hemoglobin cell, necrosis, degeneration and pigmentation occurred in body organs when up welling happened. Beside that, during up-welling digestive organ become easily breakable resulted in fish mass mortality in floating net cage. The affinity of hemoglobin to the toxic gas was higher than to oxygen, therefore aeration was not affective and mass mortality cannot be avoided. This was because of various events that occured to the fish and the other water biota that encompassed regular diffusion, bio-magnification, and bio-concentration to fish.